2020
DOI: 10.1039/d0cy01472a
|View full text |Cite|
|
Sign up to set email alerts
|

Surfactant-aided synthesis of RhCo nanoclusters as highly effective and recyclable catalysts for the hydrolysis of methylamine borane and dimethylamine borane

Abstract: In the present study, the first ever and easy surfactant-aided synthesis of hexadecyltrimethyl ammonium bromide-stabilized RhCo nanoclusters (Rh0.63Co0.37@CTAB) and their employment as highly efficient, relatively cost-saver, and recyclable catalysts to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In addition, the catalytic activity of the Pt 0.7 Ni 0.3 /CNS nanohybrid with other reported catalytic systems for H 2 generation from dimethylamineborane hydrolysis is also compared in Table . As a result, the comparison had further confirmed that Pt 0.7 Ni 0.3 /CNS exhibited the highest TOF of 16,607 h –1 at 0.3 M NaOH, which exceeded the other reported catalytic systems, in H 2 generation from dimethylamineborane hydrolysis.…”
Section: Resultsmentioning
confidence: 83%
“…In addition, the catalytic activity of the Pt 0.7 Ni 0.3 /CNS nanohybrid with other reported catalytic systems for H 2 generation from dimethylamineborane hydrolysis is also compared in Table . As a result, the comparison had further confirmed that Pt 0.7 Ni 0.3 /CNS exhibited the highest TOF of 16,607 h –1 at 0.3 M NaOH, which exceeded the other reported catalytic systems, in H 2 generation from dimethylamineborane hydrolysis.…”
Section: Resultsmentioning
confidence: 83%
“…Meanwhile, their logarithmic plots of H 2 (ln TOF) and AB concentration (ln [AB]) are nearly horizontal, indicating zeroorder kinetics with respect to AB concentrations (Figure 4c). 20,37 This rules out the cleavage of B−N and B−H bonds as the rate-determining step, when the above samples are used as catalysts. In contrast, the rates of H 2 production are obviously accelerated with the increasing catalyst (Rh) concentrations (Figure 4b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[5] However, the formation of some volatile side products such as ammonia, borazine, or diborane in the dehydrogenation of AB limits its employment in the on-board systems since they are poisonous for the fuel cells. [6,7,8] In this context, carbon derivatives of AB including methylamine borane (BH 3 NH 2 CH 3 , MeAB), [9,10] dimethylamine borane (BH 3 NH(CH 3 ) 2 , DMAB), [11] hydrazine borane (BH 3 N 2 H 4, HB), [12,13] and ethane 1,2-diamine borane ((BH 3 NH 2 CH 2 ) 2 , EDAB) [14,15] are regarded as very promising candidates.…”
Section: Introductionmentioning
confidence: 99%